PENGARUH JUMLAH ANGGOTA, VOLUME USAHA, LIKUIDITAS DAN JUMLAH KEWAJIBAN KOPERASI TERHADAP PERMINTAAN JASA AUDIT PADA KOPERASI DI KOTA BUKITTINGGI - Oriza, Yonanda; Tanjung, Amries Rusli; Hariyani, Eka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The current need for reliable financial statements, and can be trusted is necessary in making a decision. The problem in this study is whether which the effect of number of members, the business volume, liquidity and total liabilities the demand for audit service. The population in this study were 80 cooperatives and the research sample is 49 cooperatives in Bukittinggi. the dependent variables in this study are demand audit services. While the independent variables are the number of members, the business volume, liquidity and total liabilities of cooperatives. The data used in form of cooperative financial reports in fiscal year 2014 with using descriptive analysis, multicolonearitas and logistic regression with SPSS version 20. The conclusion of this research is variable number of members, liquidity and total liabilities affect on demand for audit services, while business of members does not affect the audit service.Keywords: business volume, liquidity, total liabilities, and audit